Opinion 2470: Bidessus Sharp, 1880 (Coleoptera, Dytiscidae, Bidessini): usage conserved - ICZN (Bulletin of Zoological Nomenclature, 2021)
The International Commission on Zoological Nomenclature has conserved current usage of the generic name Bidessus Sharp, 1880 by designating Dytiscus unistriatus Schrank, 1781 as its type species and suppressing Dyticus parvulus Müller, 1776 for the purposes of the Principle of Priority. The International Commission on Zoological Nomenclature has used its specific powers to confirm that authorship of the nominal taxon Dytiscus unistriatus is to be attributed to Schrank, 1781, as the work published by Goeze in 1777 is not consistently binominal and the names proposed in it are, therefore, unavailable (aside from some few that were previously ruled available by the Commission).